OF ESSENTIAL OILS FROM PLANTS AND THEIR CHANGE WITH VEGETATIVE PHASES AS AN EXAMPLE OF ASIAN MINT (MENTHA ASIATICA BORISS) (Spectrum Journal of Innovation, Reforms and Development, 2022)
Mentha asiatica Boriss. in two phases received essential oils: in the phase of vegetation and flowering. The aboveground part in the phase of the growing season contains 0.10%, in the leaves - 0.13%; the phase in the aboveground part flowering contains 0.14%, in the leaves - 0.17%, and in inflorescences - 0.23% of essential oil.